Glass transition, topology, and elastic models of Se‐based glasses. Issue 6 (22nd February 2023) - Chbeir, Ralph; Welton, Aaron; Burger, Matthew; Chakravarty, Soumendu; Dash, Shreeram; Bhosle, Siddhesh; Gunasekera, Kapila; Almutairi, Badriah S.; Goodman, Bernard; Micoulaut, Matthieu; Boolchand, Punit
Abstract: Features intrinsic to disorder and network aspects are ubiquitous in structural glasses. Among this important class of materials, chalcogenide glasses are special—they are built of short‐range covalent forces, making them simpler than silicate glasses that possess mixed ionic and covalent forces. Selenium‐based glasses also display complex elastic phase transitions that have been described from various models, including mean‐field approaches to molecular simulations. These point to the presence of two sharply defined elastic phase transitions, a rigidity and stress transition that are non‐mean‐field in character, and separate the three distinct topological phases of flexible, isostatically rigid, and stressed‐rigid. This article reviews the physics of these glassy networks. The elastic phases and glass transition temperature are explained on a molecular level in terms of topological constraint theory (TCT), connectivity, and the open degrees of freedom. The broader aspects of TCT in relation to phase change materials, high‐ k dielectrics, and cements are also commented upon.